NIL_004 Summary of session C6: Q&A-everything you wanted to know about gravitational waves but were afraid to ask - Fafone, V.; Sutton, P. J.; Cornish, N.; Reisswig, C.; Sturani, R. [UNESP]; Stuver, A. L. (Springer, 2014)
The paper summarizes the parallel session C6 Q&A-everything you wanted to know about gravitational waves but were afraid to ask of the joint 10th Amaldi Conference on Gravitational Waves and 20th International Conference on General Relativity and Gravitation.
Keywords: Gravitational radiation; Theory; Detectors; Sources